A study of Fowler-Nordheim injection mechanism for engineered tunnel barrier flash memory devices - Mohd Rosydi Zakaria (School of Microelectronic Engineering, Universiti Malaysia Perlis, 2011)
There are three main components of the project. Firstly, the conventional flash memory is model by using Fowler-Nordheim concept. Then This original model is again modified to perform based on the Engineered Tunnel Barrier (ETB) flash memory. This latter model is then used the calculate the programming time, programmming speed and programming voltage. Secondly, the devicewill be simulatedusing TCAD software in order to study its fundamental performance. The design firstly drawn using the TSUPREM-4 and then followed up with the MEDICI software to simulate the electrical characteristics. With the simulation work, it has help a lot in saving time, expensive experimental setup and expensive prototypes. The simulation works focuses on optimizing the tunnel oxide thickness, achieving a faster programming speed and reduces the programming voltage. Finally simulation and modelling results will be compared to verify the characteristic and the perfomance.